Radiological differences between HIV-positive and HIV-negative children with cholesteatoma - Mc Guire, Jessica Kate (Division of Otorhinolaryngology, 2018)
Introduction: HIV-positive children are possibly more prone to developing cholesteatoma. Chronic inflammation of the middle ear cleft may be more common in patients with HIV and this may predispose HIV-positive children to developing cholesteatoma. There are no studies that describe the radiological morphology of the middle ear cleft in HIV-positive compared to HIV-negative children with cholesteatoma. Aim: Compare the radiological differences of the middle ear cleft in HIV-positive and HIV-negative children with cholesteatoma. Method A retrospective, cross-sectional, observational analytical review of patients with cholesteatoma at Red Cross War Memorial Children's Hospital over a 6 year period. Results: Forty patients were included in the study, 11 of whom had bilateral cholesteatoma and therefore 51 ears were eligible for our evaluation. HIV-positive patients had smaller (p=0.02) mastoid air cell systems (MACS). Forty percent of HIV-positive patients had sclerotic mastoids, whereas the rate was 3% in HIV-negative ears (p<0.02). Eighty-two percent of the HIV-positive patients had bilateral cholesteatoma compared to 7% of the control group (p<0.02). There was no difference between the 2 groups with regards to aeration of the middle ear cleft, bony erosion of middle ear structures, Eustachian tube obstruction or soft tissue occlusion of the post-nasal space. Conclusion: HIV-positive paediatric patients with cholesteatoma are more likely to have smaller, sclerotic mastoids compared to HIV-negative patients. They are significantly more likely to have bilateral cholesteatoma. This may have implications in terms of surveillance of HIV-positive children, as well as, an approach to management, recurrence and follow-up. HIV infection should be flagged as a risk factor for developing cholesteatoma.